ANALISIS QS. ATH-THARIQ AYAT 10 DALAM TAFSIR JUZ ‘AMMA KARYA FIRANDA ANDIRJA - Dinda, Dinda; Hakim, Lukmanul; Jamal, Khairunnas (STAI Asy-Syukriyyah, 2024)
Firanda Andirja is not only active in direct studies but also active in conducting studies through social media such as Facebook, Instagram, YouTube videos, and personal websites. Firanda is also involved in interpretation, publishing several books of tafsir, which is something new for the salaf in Indonesia. To date, Firanda has published four tafsir books, namely Tafsir Juz 'Amma and Tafsir Juz 29, 28, 27 called at-Taysir fit Tafsir. The article will discuss the analysis of Firanda's interpretation in QS. Ath-thoriq verse 10 about his view of syafaa’at. This research method is library research, namely research whose data is taken from the form of writings or utilizing library sources. The result of this study is that Firanda still recognizes the existence of syafaat with the permission of Allah. with Allah's permission. However, humans are expected not to beg in search of such syafaat. Because, humans will bring their own good deeds. each. The understanding of assuming that a group of privileged people to be able to provide syafaat or if they assume that if the person is pleased, then he will go to heaven is a wrong understanding.